(3GdfXQjI hGdJWHjbs - (3Yha eMehO(B, (3GdcaQGhjs ((3GdGScfOQjI(B:s (3eWHYI GdGfJUGQ(B,s, 2005)
(3fTCI GdQbGHI GdeGdjI ddOhdI, CfhGY GdQbGHI Ydi GdeGd GdYGe, GdebheGJ GdCSGSjI ddYed GdQbGHj, fXe GdQbGHI Ydi GdeGd GdYGe, CSGdjH hhSGFd GdQbGHI, fXGe GdQbGHI GdeGdjI, GdQbGHI GdeGdjI aj GdOhdI GdGSdGejI, HMhK QbGHjIs
(3GdeQGLY U(B.336s
Keywords: (3GdQbGHI GdeGdjIs